Prestress Assisted Machining: Achieving high surface integrity in thin wall milling - Álvaro Sáinz de la Maza García; Luis Norberto López de Lacalle Marcaide; Gonzalo Martínez de Pissón Caruncho (Results in Engineering)
Most of the critical engineering components are subjected to cyclic thermal and mechanical loads, therefore, fatigue is the main cause of failure. As fatigue is promoted by tensile surface residual stresses, which tend to arise in machining operations, it is common to perform non-conventional post-processing operations to introduce compressive surface residual stresses; this step is costly and sometimes inefficient.This article proposes a novel machining technology to ensure compressive residual stresses near the machined surface, increasing at the same time component rigidity during milling and controlling the tendency to vibrate, which leads to lower surface roughness. This method, consists on externally applying an initial stress state to the workpiece during machining. After machining, external load is removed and residual stresses near machined surface become compressive.In addition, performed experiments and theoretical analyses showed a workpiece stiffness increase, leading to smaller cutting-force-induced deformations and almost a 200% increase in workpiece natural frequencies, permitting mitigate vibration issues with improvements of surface finish around a 30%. Machining induced surface residual stresses changed from tensile to compressive, surface damage was reduced, and burr formation decreased a 43%. In slotting operations with end-mills, prestressing induced deformations were seen, while ball-end-milling showed high geometric accuracy. Therefore, this method is ideal for very thin and slender component milling, mainly for finishing operations where tight tolerances, low roughness and high surface integrity are required.